In Vitro Inhibitory Potential of Ethanolic Extract from Nigella Sativa Seed against Glucose-Induced Lipid Glycation - Sirikwanpong, Sukrit; Marnpae, Marisa; Ariyapitipun, Tipayanate; Dahlan, Winai (Journal of Food Health and Bioenvironmental Science, 2023)
This research investigated the inhibitory effect of Nigella sativa (NS) seed extract on glucoseinduced lipid glycation by using phosphatidylethanolamine (PE) as a model. The anti-lipid glycation assay was conducted by incubating the Dioleoyl-PE (DOPE) with glucose at 37oC for 48 hr in the presence of various concentration of ethanolic NS seed extract (NSE) ranging from 5 to 40 mg/ml. Glycated-PE and carboxymethyl-PE (CM-PE) were analyzed by QTRAP mass spectrometer. The results showed that the highest concentration of NSE (40 mg/ml) significantly reduced the glycated-PE formation whereas the aminoguanidine (AG) failed to inhibit. All concentrations of NSE can inhibit the CM-PE formation, of which the reduction was greater in NSE compared to AG with the same concentration of 5 mg/ml. The significantly inverse correlations between glycated-PE and CM-PE formation with NSE concentration were also found (r = -0.919 and -0.885, respectively). Thus, our findings concluded that the ethanolic NSE had a potential to attenuate glucose-induced lipid glycation